Nutrient supply modulates species interactions belowground: dynamics and traits of fine roots in mixed plantations of Eucalyptus and Acacia mangium - Bordron, B.; Germon, A. [UNESP]; Laclau, J. P. [UNESP]; Oliveira, I. R.; Robin, A.; Jourdan, C.; Paula, R. R.; Pinheiro, R. C. [UNESP]; Guillemot, J.; Gonçalves, J. L.M.; Bouillet, J. P. (Springer Nature, 2021)
Aims: Belowground interactions are still poorly understood in mixed-species forests. We investigated the effects of soil fertility on belowground processes in mixed planted forests. Methods: The dynamics and traits of Eucalyptus and Acacia mangium fine roots (diameter < 2 mm) in plantations with 50% of each species were studied in a randomized block design established in a nutrient depleted soil. Stands with NPK fertilization applied at planting (F+) were compared to unfertilized stands (F-). Results: In the 0–15 cm soil layer, Eucalyptus root mass density (RMD) was higher than Acacia RMD by 50% in F+ and 10% in F-, considering both ages. At 34 months of age, Eucalyptus RMD was 94% higher near Acacia trees than near Eucalyptus trees in F-. In this layer, Eucalyptus specific root length (SRL) was 21% higher than Acacia SRL at 16 months of age and was 10% higher in F- than in F+ at 34 months of age. The cumulative Eucalyptus fine root length production between 16 and 34 months was 66% higher in F- than in F+ in the 0–1 m soil layer. Conclusions: Fertilization increased the competition between species and led to a partial exclusion of Acacia fine roots from the nutrient-rich topsoil. Soil exploration by Eucalyptus roots in the vicinity of Acacia trees was higher in F- than in F+, which suggests that unfertilized trees benefited from facilitation through higher soil N availability and direct N transfer from Acacia trees.
Keywords: Competition; Facilitation; Ferralsol soil; Fertilization; Mixed-species plantations